Helicobacter pylori type IV secretion, host cell signalling and vaccine development. - Backert, Steffen; Churin, Y.; Meyer, Thomas F. (Keio Journal of Medicine, 2002)
Helicobacter pylori is a bacterial pathogen specialised to colonise and persist the gastric mucosa and to cause severe gastroduodenal disease. A major disease-associated bacterial component is a type IV secretion system (TFSS) encoded by the cytotoxin-associated genes pathogenicity island (cagPAI). Among the multiple responses in H. pylori-infected epithelial cells, the induction of proinflammatory cytokines and chemokines, cell spreading and motility associated with the "hum mingbird" phenotype appear strictly dependent on the functional transporter complex in the cagPAI. H. pylori is also capable of occasionally entering epithelial cells and manipulates the host immune system for immune evasion. Attached bacteria actively translocate the CagA protein into epithelial cells by a TFSS-dependent process and translocated CagA undergoes tyrosine phosphorylation in the carboxy terminal EPIYA sequence repeat motif (Y-972) by kinases of the Src family. Furthermore, we have identified a novel TFSS in H. pylori involved in horizontal DNA-transfer. Host cell signalling events and cellular phenotypes provoked by the cagPAI, the investigation of mechanisms related to gastric cancer as well as the development of a Salmonella based live recombinant vaccine are in the focus of additional departmental activities.